Aurum, a new monotypic genus of Cetoniinae (Coleoptera: Scarabaeidae) endemic to Western Australia, Australia - Hutchinson, Paul M.; Moeseneder, Christian H. (Zootaxa, 2019)
The flower beetle genus Aurum new genus (Coleoptera: Scarabaeidae: Cetoniinae: Schizorhinini: Schizorhinina) is described. Aurum is endemic to Australia, and contains a single species, Aurum leonorensis new species, from Western Australia. The genus is compared to the most closely related Australian flower beetle genera, Diaphonia Newman, 1840, Aphanesthes Kraatz, 1880, and Chondropyga Kraatz, 1880. Ecological observations and the collecting localities are detailed for Aurum leonorensis.